2017
DOI: 10.1016/j.jdent.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory randomised controlled clinical study to evaluate the comparative efficacy of two occluding toothpastes – a 5% calcium sodium phosphosilicate toothpaste and an 8% arginine/calcium carbonate toothpaste – for the longer-term relief of dentine hypersensitivity

Abstract: Dentine hypersensitivity (DH) is a common and painful condition. Twice-daily use of a 5% calcium sodium phosphosilicate toothpaste reduces DH within 1-2 weeks of initiating use. Ongoing, twice daily use of the sensitivity toothpastes evaluated in this study was associated with continued, clinically significant improvements in DH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
3
21
0
3
Order By: Relevance
“…The air-blast stimulus could better mimic the practical situation, since patients experienced sensitivity from cold water, food or air more frequently than other stimuli. In addition, many studies showed correlation between the results of air-blast test and tactile test [29,[34][35][36]. It is recommended that at least two independent stimuli should be applied [37], so secondary outcomes such as tactile, cold water test or subjective questionnaire could provide more supporting evidence in assessing DH degree.…”
Section: Discussionmentioning
confidence: 99%
“…The air-blast stimulus could better mimic the practical situation, since patients experienced sensitivity from cold water, food or air more frequently than other stimuli. In addition, many studies showed correlation between the results of air-blast test and tactile test [29,[34][35][36]. It is recommended that at least two independent stimuli should be applied [37], so secondary outcomes such as tactile, cold water test or subjective questionnaire could provide more supporting evidence in assessing DH degree.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to mechanical, chemical and thermal stimuli was assessed using the 4-point index for each tooth, scored as: 0 = subject does not respond to temperature, chemical, mechanical stimulus; 1 = subject responds to temperature stimulus; 2 = subject responds to temperature stimulus and chemical stimulus; 3 = subject responds to temperature stimulus, chemical stimulus and mechanical stimulus [8,9].…”
Section: Safetymentioning
confidence: 99%
“…Among these agents, bioglasses offer unique properties and proven clinical efficacy. Recently introduced calcium sodium phosphosilicate (Novamin), is a particulate bioactive glass 3 which preferentially binds to exposed tubules 4 ; on exposure to the aqueous oral environment, it provides calcium and phosphate ions to form a hydroxycarbonate apatite-like layer on the dentine surface and within the tubules resulting in tubular occlusion. 5 A novel modification of Novamin, fluoro-calcium phosphosilicate, or Biomin was introduced in 2016.…”
Section: Introductionmentioning
confidence: 99%